CCR2+ monocytes infiltrate atrophic lesions in age‐related macular disease and mediate photoreceptor degeneration in experimental subretinal inflammation in Cx3cr1 deficient mice - Florian Sennlaub; Constance Auvynet; Bertrand Calippe; Sophie Lavalette; Lucie Poupel; Shulong J. Hu; Elisa Dominguez; Serge Camelo; Olivier Levy; Elodie Guyon; Noah Saederup; Israel F. Charo; et al. (EMBO Molecular Medicine, 2013)
Abstract Atrophic age‐related macular degeneration (AMD) is associated with the subretinal accumulation of mononuclear phagocytes (MPs). Their role in promoting or inhibiting retinal degeneration is unknown. We here show that atrophic AMD is associated with increased intraocular CCL2 levels and subretinal CCR2+ inflammatory monocyte infiltration in patients. Using age‐ and light‐induced subretinal inflammation and photoreceptor degeneration in Cx3cr1 knockout mice, we show that subretinal Cx3cr1 deficient MPs overexpress CCL2 and that both the genetic deletion of CCL2 or CCR2 and the pharmacological inhibition of CCR2 prevent inflammatory monocyte recruitment, MP accumulation and photoreceptor degeneration in vivo. Our study shows that contrary to CCR2 and CCL2, CX3CR1 is constitutively expressed in the retina where it represses the expression of CCL2 and the recruitment of neurotoxic inflammatory CCR2+ monocytes. CCL2/CCR2 inhibition might represent a powerful tool for controlling inflammation and neurodegeneration in AMD.